Twin Pregnancy in the Martina Franca Donkey Breed Managed by Natural Reduction and Post-Fixation Manual Crushing - Maria Cristina Veronesi; Ippolito De Amicis; Brunella Anna Giangaspero; Jasmine Fusi; Domenico Robbe; Francesco Castelli; Augusto Carluccio (Animals, 2024)
In Equids, undetected twin pregnancy represents the most important cause of abortion and is also associated with high neonatal mortality rates. Therefore, the detection and management of twin pregnancies is pivotal to allow the continuation of single pregnancies. Although pre-fixation manual crushing of one embryo is the most common management of twin pregnancies, and the impact of natural reduction has been reported in mares, very little is known about donkeys. The present study aimed to report results on the natural reduction occurrence and post-fixation manual crushing management of twin pregnancies in the Martina Franca donkey breed. Methods: Twenty-five twin pregnancies were detected at 11–13 days after ovulation. At 16 days after ovulation, twin pregnancies were classified as unilateral or bilateral and left untreated. The occurrence of natural reduction of one embryo was assessed at 20–21 days after ovulation, and post-fixation manual crushing of one embryo was performed in those cases in which natural reduction did not occur. The pregnancy rate at 28 days after ovulation and live foal rate were recorded. Result: Sixteen out of 25 twin pregnancies were unilateral and nine bilateral. At 20–21 days after ovulation, the natural reduction of one embryo occurred in 87.5% of the unilateral and in none of the bilateral twin pregnancies. The remaining twin pregnancies were treated by post-fixation manual crushing of one embryo. The 28-days-after-ovulation single embryo pregnancy rate was 93.8% for unilateral twin pregnancies and 88.9% for bilateral twin pregnancies, with an overall pregnancy rate of 92%. The live foal rate was 87%. Conclusions: The success rate of natural reduction within 20–21 days after ovulation, the 28-days-after-ovulation pregnancy rate, and the live foal rate suggest that waiting for the natural reduction of one embryo and choosing the post-fixation manual crushing of one embryo could be considered as an alternative to traditional early pre-fixation manual crushing in the Martina Franca donkey breed.